La legittima difesa come categoria alla prova: Fine della nozione di guerra giusta e problemi aperti - Eusebi, Luciano (Monitor ecclesiasticus, 2014)
The essay deals with the aim (that is typical of Canon Law, too) to "reestablish justice" in relation with unfair aggressions. It starts from the strong orientation of moral Theology and of the Magisterium that limits the direct use of force only to situations in which the legitimate defense is clear. First, the work illustrates the reasons for leaving the just war theory, having regard to a notion of justice which cannot be based anymore on the reciprocity of behaivor, to the necessity of contrasting in advance the egoistic interests which favor armed conflicts, and to the possibility of destructive effects that war can cause today for mankind. Then, the author explains why the notion of legitimate defense is actually a dorm of "imperfect" justice, linked to the presence of evil in human condition, because it does not allow to "reestablish justice" in relation with the killed aggressor. So that, it is evident the fundamental role played by the commitment to avoid conflicts, and the idea of "global citizenship" is enhanced, in order to go progressively and pacifically beyond the divisions among the nations. In this perspective, the Church can offer a specific contribution, thanks to its role of sole entity that remains autonomius from the States and has effectively universal influence. The result is a possibility to reshape the incidence of Canon Law in legal culture, because of its nature of supranational legal system.